The Coronavirus Pandemic: A Possible Model of the Direct and Indirect Impact of the Pandemic on Sleep Quality in Italians - Casagrande M (Dove Medical Press, 2021)
Maria Casagrande,1 Giuseppe Forte,2 Renata Tambelli,1 Francesca Favieri2 1Dipartimento di Psicologia Dinamica, Clinica e Salute, “Sapienza” Università di Roma, Rome, Italy; 2Dipartimento di Psicologia, “Sapienza” Università di Roma, Rome, ItalyCorrespondence: Maria CasagrandeDipartimento di Psicologia Dinamica, Clinica e Salute, “Sapienza” Università di Roma, Via Degli Apuli, Rome, 100185, ItalyEmail maria.casagrande@uniroma1.itPurpose: This study aimed to assess the direct and indirect impact of COVID-19-related aspects on self-reported sleep quality, considering the moderator role of some psychological variables.Methods: During the first weeks of the lockdown in Italy, 2286 respondents (1706 females and 580 males; age range: 18– 74 years) completed an online survey that collected sociodemographic information and data related to the experience with the COVID-19 pandemic. Some questionnaires assessed sleep quality, psychological well-being, general psychopathology, Post-Traumatic Stress Disorders symptoms, and anxiety. The path analysis was adopted.Results: The study confirms a direct effect of some aspects ascribable to the pandemic, with a mediator role of the psychological variables. Lower sleep quality was directly related to the days spent at home in confinement and the knowledge of people affected by the COVID-19. All the other aspects related to the COVID-19 pandemic influenced sleep quality through the mediator effect of psychological variables.Conclusion: This study highlighted that the psychological condition of the population has been influenced by the COVID-19 pandemic and the government actions taken to contain it, but it has also played an important role in mediating the quality of sleep, creating a vicious circle on people’s health. The results suggest that a health emergency must be accompanied by adequate social support programs to mitigate the fear of infection and promote adequate resilience to accept confinement and social distancing. Such measures would moderate psychological distress and improve sleep quality.Keywords: COVID-19, pandemic, sleep quality, psychological distress, home confinement, social isolation